Studi kasus: Penerapan Pajak Penghasilan Pasal 21 - Bonifasius Tambunan; Agnes Monica Simanjuntak (Jurnal Riset Akuntansi dan Bisnis, 2022)
Already using PTKP as stipulated in the Director of Tax Regulation No. 101/PMK.010/2016 and Article 21 PPh rates for individuals. 2. Payment of taxes and filling of Article 21 Annual SPT for the year 2021 made by employees of PT. Pabrik ES Siantar has been carried out in accordance with Law No. 36 of 2008 concerning Income Tax and General Provisions and Taxation Procedures because it has included the required data. in need. 3. The annual SPT report has been made on time, in accordance with the time period stipulated by Law Number 36 of 2008 concerning Income Tax and General Provisions and Tax Procedures so that the company is not subject to administrative sanctions.Employees of PT. Factory ES Siantar should continue to calculate Article 21 income tax, deposit and report income tax article 21 in accordance with the applicable Tax Law. However, always follow the development of the Taxation Law and the latest tax regulations stipulated by the Director General of Taxes regulations for the calculation, deposit, and reporting of PPh article 21 for the following year in order to fulfill its tax obligations properly.